Investigation on silent bacterial infections in specimens from pregnant women affected by spontaneous miscarriage. Issue 1 (5th August 2018) - Contini, Carlo; Rotondo, John C.; Magagnoli, Federica; Maritati, Martina; Seraceni, Silva; Graziano, Angela; Poggi, Alice; Capucci, Roberta; Vesce, Fortunato; Tognon, Mauro; Martini, Fernanda
Abstract : Miscarriage is one of the main complications occurring in pregnancy. The association between adverse pregnancy outcomes and silent bacterial infections has been poorly investigated. Ureaplasma parvum and urealiticum, Mycoplasma genitalium and hominis and Chlamydia trachomatis DNA sequences have been investigated by polymerase chain reaction (PCR) methods in chorionic villi tissues and peripheral blood mononuclear cells (PBMCs) from females with spontaneous abortion (SA, n = 100) and females who underwent voluntary interruption of pregnancy (VI, n = 100). U. parvum DNA was detected in 14% and 15% of SA and VI, respectively, with a mean of bacterial DNA load of 1.3 × 10 −1 copy/cell in SA and 2.8 × 10 −3 copy/cell in VI; U. urealiticum DNA was detected in 3% and 2% of SA and VI specimens, respectively, with a mean DNA load of 3.3 × 10 −3 copy/cell in SA and 1.6 × 10 −3 copy/cell in VI; M. hominis DNA was detected in 5% of SA specimens with a DNA load of 1.3 × 10 −4 copy/cell and in 6% of VI specimens with a DNA load of 1.4 × 10 −4 copy/cell; C. trachomatis DNA was detected in 3% of SA specimens with a DNA load of 1.5 × 10 −4 copy/cell and in 4% of VI specimens with a mean DNA load of 1.4 × 10 −4 copy/cell. In PBMCs from the SA and VI groups, Ureaplasma spp, Mycoplasma spp and C. trachomatis DNAs were detected with a prevalence of 1%–3%. Bacteria were investigated, for the first time, by quantitative real‐time PCR (qPCR) in chorionic villi tissues and PBMCs from women affected by SA and VI. These data may help to understand the role and our knowledge of the silent infections in SA. Abstract : Miscarriage is one of the main complications occurring in pregnancy. Silent bacterial infections in miscarriage have been poorly investigated. Our data may help to understand the role of silent infections in miscarriage.